The degree of functional capacity impairment in patients admitted to hospice care - Adamek, Jolanta; Pop, Teresa; Bejster, Anna; Pikor, Lucyna (European Journal of Clinical and Experimental Medicine, 2012)
Background. Despite advances in medicine, many patients still experience an unfavorable prognosis as to their health. The analysis conducted by the experts of the World Health Organization shows that by 2020, the average life expectancy will increase to 71.6 years. The projected increase in the number of elderly people increases the risk of developing cancer and other somatic disorders. Modern palliative care is fundamentally different from the care that was common in hospitals in the past. A range of treatment procedures has been introduced, based on the results of medical research relating to, among other things, improving the quality of life, functional capacity and psychophysical capacity in this group of patients. Objective. The aim of this study was to assess the functional capacity impairment of persons admitted to hospice care. Material and method. The test group consisted of 41 patients receiving hospice care and 41 persons in the control group. To evaluate the factors tested, Katz Scale (Index of Independence in Activities of Daily Living, ADL), Lawton Scale (Instrumental Activities of Daily Living, IADL) and Tinetti Scale have been used. The examination was performed at the time of admission of patients to hospice care. Results. Based on statistical analysis of basic and complex activities of daily living a difference in the capacity level was observed, with the test group subjects receiving poorer results. The test group achieved worse results in terms of locomotor activity such as change of the position and gait. In 56% of the subjects from the test group there was a high and medium risk of falls; in the control group large and medium risk of falls was found in 24% of subjects. Conclusions. 1. The majority of patients admitted to hospice care are characterized by severe and moderate dependence in terms of basic and complex activities of daily living and have limited locomotor capacity. 2. Lawton IADL Scale is the most sensitive one in the assessment of the loss of functional capacity. 3. Lawton scale results are comparable to the results obtained using Katz Scale and Tinetti Scale, which allows for the use of the scales interchangeably.